Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1021/acs.chemmater.5b02020
|View full text |Cite
|
Sign up to set email alerts
|

Monodipserse Nanostructured Spheres of Block Copolymers and Nanoparticles via Cross-Flow Membrane Emulsification

Abstract: Monodispersed colloidal particles of polystyrene-b-polybutadiene (PS-b-PB) block copolymers (BCPs) were successfully prepared, in which uniform emulsion containing BCPs were firstly generated by cross-flow membrane emulsification using tubular Shirasu porous glass (SPG) membrane and then unique internal nanostructures were developed by controlled evaporation of emulsions. The diameter of those BCP particles could be controlled from 200 nm to 5 µm by tuning the pore diameter of the membrane. With symmetric BCPs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
81
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(90 citation statements)
references
References 65 publications
4
81
0
2
Order By: Relevance
“…[43] As model system, we chose polystyrene-blockpolybutadiene-block-poly(tert-butyl methacrylate) (SBT) triblock terpolymers (Scheme 1a;s ee Supporting Information). [46][47][48][49][50] For our purposes,wefirst dissolved SBT in chloroform (CHCl 3 )at ac oncentration of c = 10 gL À1 ,f ollowed by emulsification in water containing cetyltrimethylammonium bromide (CTAB) (c = 10 gL À1 )a ss urfactant (Scheme 1b). Self-assembly in confinement has emerged as apowerful method to create functional block copolymer microparticles,y et, for triblock terpolymers the potential of confinement assembly is still largely unexplored.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[43] As model system, we chose polystyrene-blockpolybutadiene-block-poly(tert-butyl methacrylate) (SBT) triblock terpolymers (Scheme 1a;s ee Supporting Information). [46][47][48][49][50] For our purposes,wefirst dissolved SBT in chloroform (CHCl 3 )at ac oncentration of c = 10 gL À1 ,f ollowed by emulsification in water containing cetyltrimethylammonium bromide (CTAB) (c = 10 gL À1 )a ss urfactant (Scheme 1b). Self-assembly in confinement has emerged as apowerful method to create functional block copolymer microparticles,y et, for triblock terpolymers the potential of confinement assembly is still largely unexplored.…”
mentioning
confidence: 99%
“…Self-assembly in confinement has emerged as apowerful method to create functional block copolymer microparticles,y et, for triblock terpolymers the potential of confinement assembly is still largely unexplored. [46][47][48][49][50] For our purposes,wefirst dissolved SBT in chloroform (CHCl 3 )at ac oncentration of c = 10 gL À1 ,f ollowed by emulsification in water containing cetyltrimethylammonium bromide (CTAB) (c = 10 gL À1 )a ss urfactant (Scheme 1b). CHCl 3 was allowed to evaporate over the course of 2days to give solid SBT Scheme 1.…”
mentioning
confidence: 99%
“…Okubo et al demonstrated poly(styrene‐ block ‐methylmethacrylate) (PS‐ b ‐PMMA) microspheres having a periodic onion‐like structure, prepared by the evaporation of solvent from droplets of an emulsion in toluene . Kim and co‐workers have developed a crossflow type membrane emulsification technology to control the size of block copolymer microspheres . Yabu and co‐workers also identified onion‐like structures in phase separated PS ‐b‐ PMMA microspheres produced using the SORP technique .…”
Section: Controlling the Structures Of Phase Separated Polymer Microsmentioning
confidence: 99%
“…Stattdessen vereinen wir intrinsische Asymmetrie von ABC-Triblock-Terpolymeren mit der Selbstorganisation im beengten Raum unter Lçsungsmittel-Verdampfung (Schema 1). [46][47][48][49][50] In unserem Beispiel lçsen wir zunächst das SBT-Polymer in Chloroform (CHCl 3 )b ei c = 10 gL À1 und emulgieren die Polymerlçsung in Wasser mit Cetyltrimethylammoniumbromid (CTAB; c = 10 gL À1 )a ls Te nsid (Schema 1b). [44,45] Die Blocklängen wurden gewählt, um die Bildung einer Lamellen-Lamellen-(ll)-Morphologie zu begünstigen;d ie wichtigsten Details der Polymere sind in Tabelle 1aufgelistet.…”
unclassified
“…FürT riblock-Terpolymere ist das Potenzial dieser Methode jedoch bislang nahezu unerforscht. [46][47][48][49][50] In unserem Beispiel lçsen wir zunächst das SBT-Polymer in Chloroform (CHCl 3 )b ei c = 10 gL À1 und emulgieren die Polymerlçsung in Wasser mit Cetyltrimethylammoniumbromid (CTAB; c = 10 gL À1 )a ls Te nsid (Schema 1b). Anschließend verdampft CHCl 3 über einen Zeitraum von ca.…”
unclassified